Storage stability of chilled minimally processed shredded cabbage - Roshita Ibrahim (Universiti Putra Malaysia, 2011)
Minimally processed products are a rapidly growing segment for retail market and food service horticultural industry as they match the consumers' demand for product freshness and convenience. The shelf-life extension of these fresh-cut products is therefore relevant because of its economic impact. Packaging can be one of the important factors in determining the storage stability and quality of these freshcut products.